Het debet van het dogma - Groot, C. N. de (Tijdschrift voor theologie, 2007)
Anyone posing the question of the meaning of religion in a scientific culture is compelled to examine what it means and does in visible reality. Ritual appears to be the characteristic feature of religion. It is the inheritance that modern culture has received from its religious past. Rituals appear to have their own force rather than being merely the external packaging for religious faith. Their performance alone seems to give meaning to life because they confer a pattern upon it - and because they are performed collectively. This makes believers feel part of a larger whole, so that they feel that they are at home rather than being lost individuals. Given this, how are we to understand the meaning of religion’s content? Is it made up of the dogmatic pronouncements endorsed as a matter of course in - and the narratives recounted during - the ritual? These appear to have some relevance for the shape (established) religion assumes, but they, in their turn, appear to be shaped by history and the local situation in which they are embedded. Religious tradition seems to have a striking freedom in choosing the narratives that lie at its foundation and in determining their main focus. Religion seems to have little if any overlap with the notion ‘dogmatic’ (in its various meaning). It is a versatile source of orientation and meaning that owes its effectiveness to being open to the surrounding non-religious world.